Jewish attempts to penetrate the Arab states during the Ottoman era (1517-1920) - أمحمد أمحمد إبـراهيـم (مجلة المختار للعلوم الإنسانية, 2024)
The relationship between the Jews and the Ottoman Turks went through various phases and stages from its inception until the recognition of their state by modern Turkey in 1949. Harmony prevailed when the Jews were mere subjects in the Ottoman Empire, similar to other communities. However, there were instances of firmness by the Ottoman state when Jewish ambitions emerged, especially in the periods preceding World War I. Despite the Ottoman’s generally positive treatment of the Jews and their warm welcome, the Ottomans faced challenges in the lands from which the Jews came to the Ottoman territories. To explore these dynamics and the extent of the relationship between the two parties, a study titled "Jewish Attempts to Infiltrate Arab States during the Ottoman Era 1517-1920" was conducted. To understand these aspirations and Ottoman reactions, the study is divided into two axes. The first axis examines the general conditions of Jews in the state from its establishment until the end of the 18th century. The second axis explores Jewish efforts to settle and secure promises from the Ottoman authorities to realize their dreams through global Zionism, particularly active in the second half of the 19th century—a period marked by the decline of the Ottoman Empire and the loss of its properties in various places. Additionally, the study delves into how the Ottomans dealt with these aspirations and focuses on the official stance of the state regarding Zionist colonial alliances and interactions in the early 20th century